Improving whole wheat dough tenacity and extensibility: A new kneading process. (November 2019) - Cappelli, Alessio; Guerrini, Lorenzo; Cini, Enrico; Parenti, Alessandro
Abstract: Whole wheat bread is an important source of dietary fiber, vitamins, minerals, and antioxidants. Unfortunately, the addition of bran and middlings lead to significant rheological problems, while the bread that is produced has lower volume and increased crumb density. For these reasons, bakers need to find new strategies. This paper presents a new procedure in which the addition of bran and middlings during kneading is delayed. Our laboratory-scale experiment assessed differences in dough rheology and bread characteristics as a function of three percentages of bran and middlings content (10%, 20%, and 30%) and five addition times (0, 2, 3.5, 5, and 6.5 min after kneading begins). Total kneading time was 8 min both in rheological and breadmaking tests. Results show ameliorative effects related to the delayed addition of bran and middlings during kneading. In particular, improved dough rheology (i.e. lower tenacity and tenacity/extensibility ratio, accompanied by higher extensibility), and bread characteristics (i.e. greater specific volume) were obtained with addition at 2 min. The proposed strategy improves both dough rheology and whole wheat bread characteristics, and could guide the development of specific kneading machines for whole wheat flours. Graphical abstract: Image 106078 Highlights: Delayed addition of bran and middlings during kneading was evaluated. Three levels of bran and middlings content and five addition times were tested. Effects on dough rheology and whole wheat bread characteristics were assessed. Delayed addition at 2 min reduced dough tenacity and increased extensibility. Furthermore, it increased whole wheat bread volume and reduced crumb density.